Incidencia de la educación ambiental en huertos familiares, como forma de vida que propicia seguridad alimentaria, comunidad San Pablo de Tarugo - Solórzano Saltos, María Lisbeth (2016)
The objective of the research was to evaluate the impact of environmental education on the development of family gardens as a way of life that favors food security through the elaboration of a family garden in the Themistocles Saldarriaga Millennium Educational Unit in the community of San Pablo de Tarugo of Chone canton. It was conducted in 2016, as a type of non-experimental research. The descriptive method was used, with techniques of observation, tree of problems, participatory rural diagnosis, conversational, brainstorming and surveys. The results showed that the students, teachers and inhabitants have little knowledge of environmental education and little training on the subject; in terms of the development of ecological family gardens, had ideas of the theme, through proposals from other institutions, which were never implemented. The life experience has made the participant of the community to become sensitive and created an environmental awareness, for the sense of responsibility demonstrated in each participatory activity during the voluntary elaboration of the garden. The final product, a guide of strategies of good practices of environmental education on family-ecological gardens was proposed, as a way of life that favors the food security in the community.